Long Term Performance of a Bi-Directional Neural Interface for Deep Brain Stimulation and Recording - Stanslaski, Scott R.; Case, Michelle A.; Giftakis, Jonathon E.; Raike, Robert S.; Stypulkowski, Paul H. (Frontiers in Human Neuroscience, 2022)
In prior reports we described the design and initial performance of a fully implantable, bi-directional neural interface system for use in deep brain and other neurostimulation applications. Here we provide an update on the chronic, long-term neural sensing performance of the system using traditional 4-contact leads and extend those results to include directional 8-contact leads.